Comparing Frequency and Severity Ratings for ME/CFS versus Controls - Leonard A. Jason; Sage Benner; Nicole Hansel (Psych, 2023)
Most questionnaires for somatic symptoms focus either on occurrence, frequency, or severity, and in doing so, they might not be able to comprehensively assess the burden that symptoms present to patients. For example, a symptom might occur at a high frequency but only a minimal severity, so that it is less likely to be a burden on a patient; whereas a symptom that has both a high frequency and severity is more likely to be negatively impacting a patient. Study 1 examined frequency and severity scores for classic Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) symptoms among patients with ME/CFS versus a control group. Findings in Study 1 indicate there were more frequency/severity discrepancies for individuals with ME/CFS versus the control group. Study 1 concluded that collecting data on both measures of symptom burden provides unique indicators that can better assess the burden of the symptoms on patients. In a separate data set, Study 2 reported reliability data on slight differences in the time period and the way the severity was assessed. Study 2 findings indicated high levels of reliability for these changes in the time period and the way questions were asked. These studies provide important psychometric properties that could lead to more reliable and valid assessments of patients with post-viral illnesses.